2021
DOI: 10.1007/s10071-021-01532-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the accuracy of facial expressions as emotion indicators across contexts in dogs

Abstract: Facial expressions potentially serve as indicators of animal emotions if they are consistently present across situations that (likely) elicit the same emotional state. In a previous study, we used the Dog Facial Action Coding System (DogFACS) to identify facial expressions in dogs associated with conditions presumably eliciting positive anticipation (expectation of a food reward) and frustration (prevention of access to the food). Our first aim here was to identify facial expressions of positive anticipation a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 99 publications
(177 reference statements)
0
41
0
1
Order By: Relevance
“…Following the experimental paradigm by Bremhorst and colleagues 28 , 29 , 49 , we tested adult dogs in a situation of anticipation of food delivery and in two situations of frustration during which food was visible but unavailable to dogs and either 1) no human was visible, or 2) a female human was looking at the dog. Furthermore, we collected cortisol saliva samples before and after each test.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Following the experimental paradigm by Bremhorst and colleagues 28 , 29 , 49 , we tested adult dogs in a situation of anticipation of food delivery and in two situations of frustration during which food was visible but unavailable to dogs and either 1) no human was visible, or 2) a female human was looking at the dog. Furthermore, we collected cortisol saliva samples before and after each test.…”
Section: Discussionmentioning
confidence: 99%
“…In domestic dogs, previous research has identified several behavioural patterns and facial expressions as being indicative of negative affective states. Regarding facial expressions, backwards directed ears, tongue out and showing the sclera (“whale eye”) have been observed in a fear-related context (fireworks exposition 27 ) while flattened ears, lips part, jaw drop and the facial displacement behaviours of lips/nose lick and blink have been linked to frustration-evoking situations 28 , 29 . However, lips licking and nose lick have also been associated with positive anticipation situations, suggesting a link to general arousal (not specifically carrying a negative valence) 30 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…When an alternative is available, both interaction with the task and gazing appear to reflect motivation to obtain the inaccessible reward, with the preferred reward type differing between subjects (c.f. Bremhorst et al 2018 , 2021 ). Conversely, when no alternative is available, ‘looking back’ probably partly reflects help-seeking and partly giving up, leading to the observed negative correlations in this and other studies (Marshall-Pescini et al 2017 ; Udell 2015 ).…”
Section: Discussionmentioning
confidence: 98%